In Patients with Osteoarthritis and Rheumatoid Arthritis, Effects of Hand Physical Features on Hand Function - Deniz, Gülnihal; Kavaklı, Ahmet; Şıkoğlu, Özen Kan; Perilioglu, Ahmet Zafer; Ece, Yıldız; Ogeturk, Murat; Bılek, Furkan (My University, 2021)
Aim: Osteoarthritis and Rheumatoid Arthritis, is one of the most common joint diseases in our country and in the world. Hand joint involvement and functions are of the most important factors that determine the impacts of the disease on daily activities. We aimed to determine the impact of the disease on the daily life activities by comparing hand grip strength and joint range of motion in healthy individuals and patients. Material and Method: In this study, 166 female were included; 52 of which are healthy female, 62 of which are female patients with Rheumatoid Arthritis and 52 of which are female patients with Osteoarthritis. Grip and pinch strength were measured using the electronic hand and finger dynamometer. Standard and finger goniometer were used for range of motion measurement of wrist and fingers. Circumference and diameter of wrist and length of hand were measured with standard anthropometric measurement tools. Disability was scored by using health assessment questionnaire (HAQ). Results: Hand and finger grip strength, range of motion measurement of wrist and fingers, and measurement of wrist circumference and diameter values of all patients and healthy groups were found statistically significant difference (p<0.001). Hand length measurements of patients and healthy individuals there was no statistically significant difference (p>0.05). HAQ scores correlated negatively with grip and pinch strength were found in all individuals. Conclusion: It was observed that the impairment of anatomical integrity, decreasing of grip and pinch strength, and pain affect independent daily life activities in the patients with Osteoarthritis and Rheumatoid Arthritis.
Keywords: Genel ve Dahili Tıp; Rehabilitasyon; Romatoloji; Ortopedi